To Build Fast and Cheap”: The Formation of the Idea of Pskov’s Urban Development in the 1940s–1970s - Nechiporuk, Dmitrii M. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
This article examines the evolution of ideas on the post-war development of Pskov based on the city’s master plans. Modern Pskov with many ancient churches and fortress walls was restored after severe military destruction which had happened during the Great Patriotic War. The master plan of 1945 worked out by Leningrad architects assumed a complete ensemble building system inside the center of Pskov with the restoration of Orthodox churches as well as the relocation of industrial enterprises from the city center to the outskirts. An important feature of the new look of Pskov was to be the city center with low buildings, emphasizing the importance of ancient monuments raised from the ruins. This vision of the historical center of the city was actively defended by the restorer and architect Yu. P. Spegalsky, who, however, failed to interest the local government in his ideas. As a result, the postwar Pskov was restored and developed with an eye kept on the current needs of the city’s development. In the 1950s, the area to be built in Pskov was significantly expanded. From an open space with a view of the Trinity Cathedral and a proposed monument to Alexander Nevsky, Sovetskaya Square, the center of the city, was turned into Lenin Square, a transport junction, surrounded from different sides by new buildings, which had an important ideological meaning (Oktiabr movie theater, Trade Union House of Culture). The new master plan of 1963 was focused on mass construction of model housing and development of urban infrastructure. But this master plan did not take into account the value and importance of ancient architectural monuments. After the consolidation of the professional community in the mid-1960s in Pskov, the attitude towards the monuments began to change. This was reflected in the master plan of 1973, which tried to combine the further growth of the city and the development of Pskov as a tourist center.